The Impact of Nickel Downstreaming Policy on the Transformation of the Economic Structure of Konawe Regency, Southeast Sulawesi - Wicaksana, Muhammad Arsyad; Putri, Nur Intan Permatasari (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study analyzes the impact of the nickel downstream policy on economic structural transformation in Konawe Regency, Southeast Sulawesi. The policy, strengthened through the 2020 export ban on raw nickel ore and the acceleration of domestic smelter development, aims to increase value added, promote industrial upgrading, and stimulate regional economic growth. This research evaluates whether the policy has significantly altered the sectoral composition, employment structure, and competitiveness of the regional economy. The study applies a quantitative approach using secondary data from 2014 to 2023. Analytical tools include Location Quotient to identify sectoral specialization, Shift-Share analysis to measure regional competitiveness, and Interrupted Time Series regression to detect structural breaks after policy implementation. The analysis also examines labor reallocation patterns and investment trends to assess the depth and inclusiveness of transformation. The findings reveal a substantial structural shift from primary-sector dominance toward manufacturing-based activity. The contribution of the secondary sector increased significantly after 2020, driven by the rapid expansion of nickel processing industries. Location Quotient results confirm that manufacturing emerged as a leading and specialized sector. Shift-Share decomposition indicates a strong positive regional competitive effect, suggesting that local industrial growth exceeded national trends. Interrupted Time Series analysis identifies a statistically significant structural break following policy enforcement, confirming that the downstream policy accelerated the growth trajectory of the manufacturing sector. Despite these gains, the transformation remains capital intensive and concentrated in nickel processing. Employment absorption in manufacturing increased but did not match the pace of output expansion. Industrial diversification beyond nickel processing remains limited. The study concludes that the nickel downstream policy has successfully initiated economic structural transformation in Konawe Regency. However, sustainable and inclusive development requires broader industrial diversification, stronger human capital development, technological upgrading, and effective environmental governance.